(untitled) (Clinics, 2012)
OBJECTIVE: Many changes in mucosal morphology are observed following ileal pouch construction, including colonic metaplasia and dysplasia. Additionally, one rare but potential complication is the development of adenocarcinoma of the reservoir. The aim of this study was to evaluate the most frequently observed histopathological changes in ileal pouches and to correlate these changes with potential risk factors for complications. METHODS: A total of 41 patients were enrolled in the study and divided into the following three groups: a non-pouchitis group (group 1) (n = 20; 8 males; mean age: 47.5 years) demonstrating optimal outcome; a pouchitis without antibiotics group (group 2) (n = 14; 4 males; mean age: 47 years), containing individuals with pouchitis who did not receive treatment with antibiotics; and a pouchitis plus antibiotics group (group 3) (n = 7; 3 males; mean age: 41 years), containing those patients with pouchitis who were administered antibiotics. Ileal pouch endoscopy was performed, and tissue biopsy samples were collected for histopathological analysis. RESULTS: Colonic metaplasia was found in 15 (36.6%) of the 41 patients evaluated; of these, five (25%) were from group 1, eight (57.1%) were from group 2, and two (28.6%) were from group 3. However, no correlation was established between the presence of metaplasia and pouchitis (p = 0.17). and no differences in mucosal atrophy or the degree of chronic or acute inflammation were observed between groups 1, 2, and 3 (p>;0.45). Moreover, no dysplasia or neoplastic changes were detected. However, the degree of mucosal atrophy correlated well with the time of postoperative follow-up (p = 0.05). CONCLUSIONS: The degree of mucosal atrophy, the presence of colonic metaplasia, and the degree of acute or chronic inflammation do not appear to constitute risk factors for the development of pouchitis. Moreover, we observed that longer postoperative follow-up times were associated with greater degrees of mucosal atrophy.